Umbilical vein. Its use in vascular surgery - Gastambide, Carmelo; Beguiristain, Alberto; Servetti, Eduardo; de Simone, Gustavo; Aramburu, Ana María; Bonaba, Roberto (Cirugía del Uruguay, 1977)
The methods for preserving and isolating the vein in human umbilical cord for use in vascular grafting are evaluated. The author concludes that the most advantageos manner of preserving it is in sterile glicerine at 95 % and that it can easily be isolated by means of .Mayo's phleboextractor combined with obtuse dissection. Veins obtained are of good lerigth, good diametre, uniform throughout, avalvular and flexible, with neithe folds nor angles.